Study on filling mining technology for gently inclined thin to medium thick phosphorus deposits - Hou, Di; Xu, Mengchao; Li, Xiaoshuang; Wang, Jiawen; Wang, Menglai; Li, Shujian (Frontiers in Earth Science, 2023)
This study is grounded in research conducted at the Kunyang Phosphate Mine No. 2, a Chinese open-pit phosphate mining enterprise owned by the Yunnan Phosphate Group Co., Ltd. Due to the small inclination angle and the presence of weak interlayers in the middle of the gently inclined thin to medium thick phosphate ore layer, mining such ore bodies cannot rely on self weight migration, making roof management difficult and mining costs high technical challenges. The methods utilized on-site research, engineering comparisons, and theoretical analysis experiments to address the gently inclined phosphorus deposits. Based on the actual technical and economic conditions of current phosphorus mines, the advantages, disadvantages, and practical conditions of upward horizontal layered filling mining method, upward horizontal layered drift filling mining method, and pseudo inclined segmented strip filling mining method are compared. Priority should be given to using the pseudo inclined segmented strip method as the main method for mining, supplemented by the upward horizontal layered filling method in the panel area. And theoretical calculation methods were applied to obtain various numerical values of the filling capacity of the 2 million t/a mine filling test section, providing technical support for the mining design and equipment selection of the filling test system. The relevant research results can provide guidance for the selection of mining methods for gently inclined thin to medium thick phosphate deposits with an average inclination angle of 15°. The theoretical calculation method used can provide technical guidance for the filling system and filling equipment.